Understanding as an epistemic virtue : a value-driven non-factive account - Rybko, Caitlin (Rhodes University, Faculty of Humanities, Department of Philosophy, 2017)
Understanding has been somewhat undervalued and underexplored in the current literature and often its value is tied into that of either truth or knowledge. This thesis aims to provide an account of understanding that defends its value as an epistemic good that is not contingent on either knowledge or truth. I will aim to construct an account that is value driven rather than nature driven as it seems that this is where the problem lies. In order to do this I will assess two current accounts of understanding and show that they cannot adequately explain the value that we give to understanding, nor do they explain how we understand.
Keywords: Uncatalogued